Remaja Sehat dalam Bersosialisasi - Alfi Noviyana; Nofita Tri Lestari; Devi Sovina (LPPM Akbid Harapan Ibu Pekalongan, 2020)
Adolescents who live in orphanages are certainly different from teenagers who live at home with a complete family. These teenage partners are more vulnerable to various problems, including social, psychological and reproductive health problems. The purpose of this service activity is to provide information and knowledge related to social health and various risks that can be experienced by adolescents. To train adolescents to seek help if they cannot solve the problems they are facing. This service activity uses the facilitation method. The activity begins with a pre test and ends with a post test. Facilitation activities were carried out 2 times. Activities followed by partners consistently and actively. The result of this activity is an increase in partner knowledge, reflected in an increase in post test scores, partners are able to demonstrate problem identification skills and interpersonal communication skills, and are willing to express opinions. The obstacle to this activity is that the community service team has not been able to become a companion for partners who are facing social problems, so the team reports and discusses them with the caregivers of the female orphanage, about the findings of problems faced by partner participants. The conclusion of this service activity increases partners' insights and knowledge about mental health, healthy friendships and social pressures that they can experience. So that you understand, what must be done to overcome the psychological problems faced.